2021
DOI: 10.3389/fpsyg.2021.769707
|View full text |Cite
|
Sign up to set email alerts
|

Grit and Meaning in Life of Chinese Nurses: The Chain Mediating Effect of Social Support and Hope

Abstract: Grit is defined as perseverance and passion for long-term goals, and it may affect the stability of the nursing workforce and the physical and mental health of nurses continuously. Meaning in life has received considerable attention from scholars, which is an important component in positive psychology. This study aimed to delve into the relationship between grit and the meaning in life of Chinese nurses. Additionally, we also sought to prove the chain mediating effect of social support and hope on this relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 61 publications
4
19
1
Order By: Relevance
“…While statements such as 'I finish whatever I begin ' and 'Setbacks don't discourage me ' show the participants' tenacity and resilience, demonstrating their grit. Grit, which is defined as “persistence and desire for long-term aspirations” ( Duckworth, 2016 , p. 1087), may have an enduring impact on the mental and physical well-being of nursing students, especially during the pandemic ( Yang & Wu, 2021 ). A correlation between grit and positive thinking was identified among high school students, with a statistically significant positive correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While statements such as 'I finish whatever I begin ' and 'Setbacks don't discourage me ' show the participants' tenacity and resilience, demonstrating their grit. Grit, which is defined as “persistence and desire for long-term aspirations” ( Duckworth, 2016 , p. 1087), may have an enduring impact on the mental and physical well-being of nursing students, especially during the pandemic ( Yang & Wu, 2021 ). A correlation between grit and positive thinking was identified among high school students, with a statistically significant positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, positive thinking focuses on the positive aspects of a situation, which is frequently referred to as an optimistic perspective ( New Jersey State Nurses Association, 2022 ; Sherwood, 2021 ). According to the fundamental tenet of positive thinking, one should approach all aspects of life to expect everything to work out well ( Yang & Wu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found a chain of significant indirect effects of functional impairment on emotional distress and quality of life that was mediated by social support and hope. Recent studies ( 50 52 ) have shown similar serial mediating roles for social support and hope in the prediction of life meaning, life satisfaction, and depressive symptoms in various patient groups.…”
Section: Discussionmentioning
confidence: 91%
“…In healthcare, possessing the qualities of grit helps healthcare workers perform better in crisis situations, assists in the quality of patient care being provided, can affect healthcare professionals’ job involvement and reduce burnout ( Jeong et al, 2019 ; Tyer-Viola, 2019 ; Lee et al, 2021 ) The study of grit also exists in other dimensions of positive psychology. Due to the increased importance of enhancing meaning-making ( Russo-Netzer, 2019 ), grit has been found to generate hope, meaning in life and 195 also leads to enhanced levels of flourishing ( Vela et al, 2015 ; Valdez and Datu, 2021 ; Yang and Wu, 2021 ). Subjective well-being is also associated with grit ( Kwon, 2021 ).…”
Section: Introductionmentioning
confidence: 99%